Exogenous testosterone increases men's perceptions of their own physical dominance. (February 2016) - Welling, Lisa L.M.; Moreau, Benjamin J.P.; Bird, Brian M.; Hansen, Steve; Carré, Justin M.
Highlights: Testosterone or a placebo was administered to healthy adult men using a within-subjects design. Self-perceptions of physical dominance were assessed using a novel 'pick-your-own-face' task. Men picked a more dominant-looking version of their own face after testosterone versus placebo. The effect that was particularly pronounced among men with relatively low baseline testosterone. Exogenous testosterone can modulate men's perceptions of their own physical dominance. Abstract: Men's testosterone is associated with several constructs that are linked to dominance rank, such as risk-taking, mating success, and aggression. However, no study has directly tested the relationship between men's self-perceived dominance and testosterone using an experimental design. We employed a within-subjects, double-blind, placebo-controlled paradigm to assess whether testosterone influences men's self-perceived dominance. Exogenous testosterone or a placebo was administered to healthy adult men and self-perceptions of physical dominance were subsequently assessed by having participants select what they believed to be their true face from an array of images digitally manipulated in masculinity. Men picked a more masculine version of their own face after testosterone versus placebo—an effect that was particularly pronounced among men with relatively low baseline testosterone. These findings indicate that a single administration of testosterone can rapidly modulate men's perceptions of their own physical dominance, which may explain links between testosterone and dominance-related behaviors.